The impact of parental migration on screen exposure among children aged 1-66 months in rural China - Yuxuan Zhu; Yating Cheng; Tao Sun; Ying Wang; Guanlan Zhao; Xiaohe Wang; Feng Wang (BMC, 2024)
Abstract Background Screen exposure, particularly recreational screen exposure, is an integral part of children's lives. However, little is known about how family factors influence children's excessive screen exposure, especially in the context of 69 million left-behind children experiencing parent-child separation in China. This study mainly concentrates on the correlation between parental migration, type of caregiver, depression and disciplinary practices of the caregiver and children's screen exposure, including average daily screen time (on weekdays or weekends) and screen content (recreational activities or learning activities). Methods For a cross-sectional study, we collected data of family basic features, parental migration status and children's screen use in the past week from caregivers of 1,592 children aged 1-66 months in Anhui province. Children were classified into left-behind children (LBC), previously left-behind children (PLBC) and never left-behind children (NLBC) based on their parental migration. Multiple linear regression and binary logistic regression were used to identified the association between family factors and children's screen exposure. Results Overall, PLBC had higher rates of screen exposure, as well as higher average daily exposure times, than NLBC and LBC. The results of logistic regression showed that PLBC had a higher likelihood of excessive screen use compared to NLBC (60 min/day, OR = 1.40, p < 0.05; 120 min/day, OR = 1.76, p < 0.05). The higher the score of disciplinary practices, the less time children spent on screens for entertainment (B = -3.37, p < 0.01). Conclusions Our findings provide insights into the risks of children's screen exposure in different contexts of parental migration. The study emphasizes the urgent need to pay attention to PLBC's screen use and to strengthen caregivers' discipline and supervision over children's screen exposure.